Development of Cephradine-Loaded Gelatin/Polyvinyl Alcohol Electrospun Nanofibers for Effective Diabetic Wound Healing: In-Vitro and In-Vivo Assessments - Anam Razzaq; Zaheer Ullah Khan; Aasim Saeed; Kiramat Ali Shah; Naveed Ullah Khan; Bouzid Menaa; Haroon Iqbal; Farid Menaa (Pharmaceutics)
Diabetic wound infections caused by conventional antibiotic-resistant Staphylococcus aureus strains are fast emerging, leading to life-threatening situations (e.g., high costs, morbidity, and mortality) associated with delayed healing and chronic inflammation. Electrospinning is one of the most widely used techniques for the fabrication of nanofibers (NFs), induced by a high voltage applied to a drug-loaded polymer solution. Particular attention is given to electrospun NFs for pharmaceutical applications (e.g., original drug delivery systems) and tissue regeneration (e.g., as tissue scaffolds). However, there is a paucity of reports related to their application in diabetic wound infections. Therefore, we prepared eco-friendly, biodegradable, low-immunogenic, and biocompatible gelatin (GEL)/polyvinyl alcohol (PVA) electrospun NFs (BNFs), in which we loaded the broad-spectrum antibiotic cephradine (Ceph). The resulting drug-loaded NFs (LNFs) were characterized physically using ultraviolet-visible (UV-Vis) spectrophotometry (for drug loading capacity (LC), drug encapsulation efficiency (EE), and drug release kinetics determination), thermogravimetric analysis (TGA) (for thermostability evaluation), scanning electron microscopy (SEM) (for surface morphology analysis), and Fourier-transform infrared spectroscopy (FTIR) (for functional group identification). LNFs were further characterized biologically by in-vitro assessment of their potency against S. aureus clinical strains (N = 16) using the Kirby–Bauer test and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, by ex-vivo assessment to evaluate their cytotoxicity against primary human epidermal keratinocytes using MTT assay, and by in-vivo assessment to estimate their diabetic chronic wound-healing efficiency using NcZ10 diabetic/obese mice (N = 18). Thin and uniform NFs with a smooth surface and standard size (<400 nm) were observed by SEM at the optimized 5:5 (GEL:PVA) volumetric ratio. FTIR analyses confirmed the drug loading into BNFs. Compared to free Ceph, LNFs were significantly more thermostable and exhibited sustained/controlled Ceph release. LNFs also exerted a significantly stronger antibacterial activity both in-vitro and in-vivo. LNFs were significantly safer and more efficient for bacterial clearance-induced faster chronic wound healing. LNF-based therapy could be employed as a valuable dressing material to heal S. aureus-induced chronic wounds in diabetic subjects.